Nexus between bank capital and risk-taking behaviour: Empirical evidence from US commercial banks - Faisal Abbas; Shoaib Ali; Syed Moudud-Ul-Huq; Muhammad Naveed (Cogent Business & Management, 2021)
The study aims to investigate the effect of conventional capital ratio, risk-based capital ratio, and capital buffer ratio on commercial bank risk-taking over the period from 2002 to 2019 using a two-step GMM method. The finding reveals that there is a positive relationship between traditional capital ratio and risk-taking for the full sample results, which is supported by the regulatory hypothesis. The results are same across various categories based on capitalization and liquidity. Whereas the relationship is negative when capital is measured through risk-based capital ratio and capital buffer, the results are in line with the moral hazard hypothesis. The outcomes are consistent for all subcategories other than for well-capitalized and low liquid banks. The full sample findings are consistent when risk is proxied through loan loss provision. The impact of capital ratios on risk-taking in the pre-, pro- and post-crisis eras is heterogeneous and significant. The findings have significant insights for regulators to observe the differences among pre-, pro- and post-crisis periods for the well, adequately, under, significantly under-capitalized, high and low liquid insured commercial banks of the USA.
Keywords: G21; G28; G32; 650; Traditional Capital Ratio; Risk-based Capital Ratio; Capital Buffer Ratio